Egipto recepcija Herodoto Istorijoje - Kardelis, Naglis (Literatūra, 2015)
The article focuses on some of Herodotus’s achievements and failures in his account of Egypt and its history presented in Books II–III of his Histories. It is argued that Herodotus describes, not only Egyptian geography, geology, meteorology, botany, and zoology, but also Egyptian religion and culture, for the most part as a naturalist, similar to his Ionian predecessors, in particular Milesian logographs and first philosophers of „nature“ (phusis), or, to say the least, as an historian with very strong leanings of a naturalist. He achieves his best results when he observes those areas of Egypt’s nature and civilization that can be described in spatial, not in temporal, terms. In particular, this is true with respect to Herodotus’s descriptions of Egypt’s natural world and ancient Egyptian architecture of the Late Period, especially the monuments of the Lower Egypt. As we can judge from his text, Herodotus is very keen to deal with all kinds of spatial patterns. He is especially eager to describe the structural complexity of Egyptian temples and other buildings, such as the Labyrinth. In fact, Herodotus is an empiricist who likes to deal with pure facts, with phenomenal particulars that can be analyzed extensionally, without recourse to the search for the inner meaning of any kind. But he is at his worst when he comes to grips with intentional, especially symbolical, sophistication of Egyptian civilization. For example, Herodotus’s failure to understand the symbolism of cyclical time that is evident in his description of the Phoenix proves his inability to understand the essence behind the surface of cultural phenomena. Yet Herodotus notices the merging of natural and cultural spheres that is specific to ancient Egyptian worldview. Quite paradoxically, this observational result is very significant not only empirically, but also theoretically. Rather unexpectedly, Herodotus who satisfactorily deals only with pure empirical data, came to realize this theoretically important cultural fact. To sum up, Herodotus’s results are mixed. In positive terms, he gets some important observational results. And in negative terms, when he fails to understand some aspects of Egyptian civilization, he unintentionally spells out and makes us notice those features of Greek mentality that are hindering his intellectual encounter with a radically different culture.